2020
DOI: 10.17509/ijal.v10i1.25034
|View full text |Cite
|
Sign up to set email alerts
|

Problems following topic shift in interactions with repaired cleft children

Abstract: Children with a history of cleft lip and/or palate (CL/P) can experience a range of difficulties such as sound articulation errors and reduced psychosocial functioning. This causes interaction with them to contain more frequent communication breakdowns than non-cleft children. The present study shows evidence of such breakdowns involving topic shifts in the interaction between parents and their repaired CL/P children. Interactional data were obtained through a series of recordings of three parent-child sets. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…These problems are believed to be the result of linguistic constraints prior to corrective surgery such as a smaller phonetic inventory size (Morris & Ozanne, 2003), compensatory articulation (Philip et al., 2018) and limited expressive vocabulary (Sedaghati et al., 2016). Studies have also reported problems within the area of pragmatic functioning that include constant failure by the children to reply adequately and accurately to their conversational partners (Frederickson et al., 2006) and difficulty for them to follow topic shifts (Saad et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems are believed to be the result of linguistic constraints prior to corrective surgery such as a smaller phonetic inventory size (Morris & Ozanne, 2003), compensatory articulation (Philip et al., 2018) and limited expressive vocabulary (Sedaghati et al., 2016). Studies have also reported problems within the area of pragmatic functioning that include constant failure by the children to reply adequately and accurately to their conversational partners (Frederickson et al., 2006) and difficulty for them to follow topic shifts (Saad et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also receive fewer positive responses from their peers. In another study, Saad et al (2020) documented the difficulties for repaired CL/P children to follow topic shifts which could be linked to their poor attention or cognitive functioning when they participate in everyday interaction. This is not unexpected as there has been evidence to suggest that their language and general cognitive functioning is significantly poorer than that of non-CL/P individuals (Roberts et al, 2012).…”
Section: Introductionmentioning
confidence: 99%